The use of Multiple Intelligences Theory in Reading Comprehension A Case Study of Third Year English Students at the University of Laghouat - CHATTI, Bouziane; CHENIEF, Bachir; GASMI, Mustapha (Faculty of Letters and Foreign Languages Department of English, 2016)
Multiple intelligence theory suggests that there are many ways people understand and perceive the world. This theory developed by Harvard psychologist Howard Gardner helped teachers, parents and learners to understand the importance of individual differences in terms of learning style. This present research tries to investigate the use of multiple intelligence theory in reading comprehension. The research started by identifying learners‘ multiple intelligence profiles of twenty English students using Walter McKenzie‘s survey (1999) to know the learners dominant intelligence. Moreover, all students were asked to answer TOEFL reading comprehension test to evaluate their reading ability. Results of correlation analysis showed that there is a strong relationship between learners multiple intelligence profiles and their reading abilities. Other results showed that naturalistic and interpersonal intelligences reacted as a predictor of learner‘s reading abilities. Further results indicate that high achievers in reading may have lower musical intelligence. In other words, the best readers may be less intelligent ‗musically‘.